Hubungan Antara Pola Asuh Orang Tua Dan Prestasi Belajar Siswa - Yasturi; Abdul Rouf; Dian Triana (Arsy : Jurnal Studi Islam, 2019)
This study aims to determine whether there is a relationship between parents' parenting and student achievement MTs An-Nidzom Babadan Kunjang Kediri. Hopotesis posed no relationship between parents' parenting and student achievement MTs An-Nidzom Babadan Kunjang Kediri 2016-2017 school year. The data collection used questionnaires and documents for the parents' parenting variables and variable student achievement. This research is quantitative. The subjects of this study were students Mts An-Nidzom Babadan Kunjang Kediri 2016/2017 academic year consisting of 89 students. Data analysis technique used Product Moment Correlation from Karl Person. Further, the process of data analiss performed with SPSS (Statistical Package For Sciences) 16:00 Windows. From the analysis stated that the respondents to the Discipline taught in MTs An-Nidzom Babadan Kunjang Kediri is the category was evidenced by the respondents amounted to 89 respondents or 60% chose the final score at the interval 50-63. There is a relationship between parents' parenting and learning achievement Academic Year 2016-2017. Based on the overall hypothesis testing conducted by F test, performed in accordance to the annex ANOVA F column, obtained calculated F value of 24 002 and F table with α = (0.05) df = n - k-1 = 89-1-1 = 87 so that the F table = 3.95. This value indicates that the value of F count> F table (24 002> 3.95). And hipotesin calculation by using analysis of coefficient of determination (R2) This means that there is a connection simultaneously learning Discipline (X) to the dependent variable (Y) that is Achievement for 0602 (60%). Thus, in this study we can conclude that the working hypothesis (Ha) which states: "The relationship between parenting parents ddan student achievement MTs An-Nidzom Babadan Kunjang Kediri" acceptable ". While the null hypothesis (H0) that states: The relationship between parenting parents and student achievement MTs An-Nidzom Babadan Kunjang Kediri 2016-2017 school year '' rejected '